DEVELOPMENT OF E-MODULE OF ABSTRACT CONCEPTS OF MATERIAL CHANGES IN THE FORM OF OBJECTS TO IMPROVE THE CRITICAL THINKING SKILLS OF AUTISTIC CHILDREN - Hasbi Arsanti; Edi Purwanta; Akbar Bagaskara; Ayu Primarini (International Journal of Cultural and Social Science, 2026)
The research aims to: (1) produce e-modules of abstract concepts of material changes in the form of objects that are appropriate to improve the critical thinking of autistic children, (2) produce e-modules of abstract concepts of material changes in the form of objects to improve the critical thinking of autistic children that are practically used by teachers and students, and (3) produce e-modules of abstract concepts of material changes in the form of objects that are effective in improving the critical thinking of autistic children. This research was development research or research and development (R&D), using the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects in this study were seven autistic students, with two students as test subjects and five students as effective test subjects. Data collection techniques used were interviews, expert questionnaires, educator response questionnaires, and tests to understand abstract concepts of material changes in the form of objects. The data analysis used was qualitative and descriptive, presented in the form of graphs. The effectiveness test was carried out by comparing the scores of the pretest and posttest before and after using the e-module of abstract concepts of material changes in the form of objects. The results of research and development include: (1) the e-module of abstract concepts of material changes in the form of objects is declared to be very feasible in supporting the learning of autistic children with an average score of 48.5 from 47 material experts and 50 media experts, (2) the results of the practicality of the e-module abstract concepts of material changes in the form of objects from the questionnaire of educators responses with an average score of 4.85 in the very practical category, and (3) the e-module of abstract concepts of material changes in the form of objects can improve the ability of critical thinking of autistic children, as indicated by the average score of the Normalized Gain Test of 0.66 (moderate).